2019
DOI: 10.1021/acsomega.9b01793
|View full text |Cite
|
Sign up to set email alerts
|

H-Content Is Not Predictive of Perfluorocarbon Ocular Endotamponade Cytotoxicity in Vitro

Abstract: In recent years, cases of retinal toxicity occurred in some European, Middle Eastern, and South American countries following the use of perfluorocarbon liquids (PFCLs) on vitreoretinal surgeries owing to impurities in the product. Moreover, Spanish ophthalmologists reported several toxic cases on the use of perfluoro- n -octane Ala Octa (Alamedics, Dornstadt, Germany), raising the necessity of reviewing the current validated methods used for assessing the safety of PFCLs. We proved that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…The findings in this study are in agreement with the results obtained by Ruzza et al, 18 who studied the extent of ARPE-19 and BALB3T3 cell mortality after the application of 1H-PFO, PFOA, and 5H-PFO at three of the concentrations tested in this study and Romano et al's. 15 The toxicity threshold assessed for PFOA and DFH in this study only slightly differed from those evaluated by Srivastava et al, 17 who found that PFOA at 0.06 mM was close to the toxicity limit, which corresponded to 25 ppm versus CC 30 of 17 ppm determined in our study, and DFH was toxic at 4.48 mM (corresponding to 1488 ppm vs. 1173 ppm in our study).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings in this study are in agreement with the results obtained by Ruzza et al, 18 who studied the extent of ARPE-19 and BALB3T3 cell mortality after the application of 1H-PFO, PFOA, and 5H-PFO at three of the concentrations tested in this study and Romano et al's. 15 The toxicity threshold assessed for PFOA and DFH in this study only slightly differed from those evaluated by Srivastava et al, 17 who found that PFOA at 0.06 mM was close to the toxicity limit, which corresponded to 25 ppm versus CC 30 of 17 ppm determined in our study, and DFH was toxic at 4.48 mM (corresponding to 1488 ppm vs. 1173 ppm in our study).…”
Section: Discussionsupporting
confidence: 93%
“…The risk of presence or appearance of potentially toxic substances in PFCL-based medical devices used as vitreous tamponades needs to be excluded by the manufacturers using accurate analytical methods and adequate safety criteria for their clinical use. 6 - 8 , 11 , 18 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These, and other examples with other medical devices for intraocular use, have resulted in our insistence that, in addition to chemical analyses ensuring an acceptable degree of purity, companies should be forced to carry out cytotoxicity studies on each batch. Toxicity, in our opinion, is not a simple matter related to the percentage of purity (obviously, the purer the better) but mainly to the nature of the contaminants, which, depending on the compound, can be highly cytotoxic even at very low concentrations; this has been demonstrated for acids or side products from manufacturing as in the case of BIO OCTANE PLUS 2,6 . Table 2 summarizes information on reported toxicity cases of PFO from the three different manufacturers, Meran, AlaMedics and Biotech.…”
Section: Discussionmentioning
confidence: 98%
“…Although it may be a desirable kind of index, a direct relationship between H index and toxicity has not yet been demonstrated. 14,15 Some companies seem to find it difficult to accept that there have been hundreds, probably thousands, of cases of blindness with these products (e.g. from toxic batches of AlaOcta ® more than 1,000 samples were distributed in Spain alone, although there is information only on 117 officially affected cases), and that a close collaboration between industry and clinicians is of paramount importance.…”
Section: What Is the Position Of The Manufacturers?mentioning
confidence: 99%